Validation of the Tunisian Social Situation Instrument in the General Pediatric Population - Rajhi, Olfa; Halayem, Soumeyya; Ghazzai, Malek; Taamallah, Amal; Moussa, Mohamed; Abbes, Zeineb Salma; Hajri, Malek; Ben Yahia, Houda; Touati, Maissa; Fakhfakh, Radhouane; Bouden, Asma (Frontiers in Psychology, 2020)
Background In order to better understand the deployment of the theory of mind (ToM) in Tunisian neurotypical children, we have developed a new tool of assessment of the ToM called the “Tunisian Social Situations Instrument” (TSSI). We opted for the creation of this test in view of the intercultural differences in the development of social skills. Our purpose was to validate this tool in general pediatric population. Methods It was a cross-sectional evaluative study that aimed to validate the TSSI in the general pediatric population. We initially conducted a beta test and a pre-validation study before taking the initial version of the TSSI on 123 neurotypical children. Then, we followed the typical validation procedure: appearance validity, content validity, construct validity, and reliability study. Results Regarding the validity of appearance, the TSSI was comprehensible and adapted to the Tunisian pediatric population. About content validity, the exploratory factor analysis extracted 6 factors that explain 69.3% of the total variance. These factors were respectively social clumsiness types 1 and 2, intention attribution, emotional ToM, epistemic ToM, and simple comprehension questions. The subdomains of social clumsiness (types 1 and 2) and emotional ToM had a Cronbach alpha higher than 0.8. This factor structure as well as the significant inter-correlation between subdomains and the global score were in favor of a good construct validity. The internal consistency study showed good reliability of the final version of the TSSI (alpha of Cronbach at 0,809). Regarding the performance of children at the TSSI, we have noticed a significant association between the global score, age, and verbal intelligence. Conclusion This work offers valuable insights about ToM and provides clinicians with a reliable tool to assess social clumsiness and emotional ToM in typically developing children.